CUSTOMER INTIMACY VALUE STRATEGY BY IMPLEMENTING CUSTOMER RELATIONSHIP MANAGEMENT - Siti Asiyah (Journal of Applied Management and Business, 2020)
This article talks about a lot of systems to transform customers into resources proposed for organizations while making faithful customers. The technique that is the focal point in this article is customer Relationship Management (CRM). This is on the grounds that without a CRM system, organizations neglect to reap the advantages of CRM. CRM is fundamentally significant for the organization's future. CRM innovation empowers organizations to all the more likely comprehend customer conduct, foresee their conduct later on, give altered customer encounters, and assemble long haul customer connections. Nonetheless, given that CRM is just restricted by innovation it will be a serious mix-up for the organization. Organizations can't give excellent customer worth, administration and experience just by putting resources into CRM innovation. This article depicts customer life cycle the executives and proposes an all encompassing system for customer life cycle the board. This section finishes by examining methodologies for transforming customers into resources and making satisfied customers.